2017
DOI: 10.1163/15685381-00003085
|View full text |Cite
|
Sign up to set email alerts
|

Osteology, fossil record and palaeodiversity of the European lizards

Abstract: Abstract. The capability of palaeontologists to identify fossil remains of a particular group of vertebrates strongly depends on the knowledge they have of its comparative osteology and on the actual presence of diagnostic differences among the considered taxa. This could have a relevant influence on the study of palaeodiversity, since a low recognisability causes a loss of data when trying to reconstruct the history of taxa that lived on Earth in the past. Currently, more than 6000 extant species of lizards a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…Additionally, Kimura et al (2016) demonstrated that the appearance of diagnostic features 869 is delayed in respect to lineage splitting in murid mammals. High intraspecific variability among 870 osteological features has also been shown in the lacertid lizard Lacerta (Villa et al 2017), where no 871 single trait could be identified as a unique, unambiguous autapomorphy of a species; rather, only 872 combinations of traits were found to be species-specific. 873…”
Section: Species Delimitation 821mentioning
confidence: 89%
See 3 more Smart Citations
“…Additionally, Kimura et al (2016) demonstrated that the appearance of diagnostic features 869 is delayed in respect to lineage splitting in murid mammals. High intraspecific variability among 870 osteological features has also been shown in the lacertid lizard Lacerta (Villa et al 2017), where no 871 single trait could be identified as a unique, unambiguous autapomorphy of a species; rather, only 872 combinations of traits were found to be species-specific. 873…”
Section: Species Delimitation 821mentioning
confidence: 89%
“…2017), and also extended implied weighting seemed to work well under certain circumstances when analysing specimen-level data in lizards (Villa et al . 2017). One reason for these discrepant conclusions could be that the modelled phylogenies did not accurately represent a real distribution of homoplasy within a morphological dataset (Goloboff et al .…”
Section: Methodological Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Smaller remains of lacertids, whose identification is notoriously tricky (Villa et al 2017), have been attributed only to indeterminate members of the family. They could represent another smaller species, but also juveniles of Lacerta gr.…”
Section: Identificationmentioning
confidence: 99%